Rubber plantation labor and labor movements as rubber prices decrease in southern Thailand - Uraiwan Tongkaemkaew; Bénédicte Chambon (Forestry Faculty, Universitas Hasanuddin, 2018)
A decrease in rubber prices can initiate labor migration trends from rubber production to industrial or service sectors, which could further cause labor shortages in rubber production. This case was not studied in the different communities with a long history of rubber such as the center city of southern Thailand. This study analyzes the source of labor and movement of laborers working in rubber plantations in the context of decreasing rubber prices. We selected 3 representative areas, namely rural, suburban and urban communities in Hat Yai district, Songkhla province. Owners of rubber holdings were the target group for the survey, and individual interviews were conducted. We collected data between March and July 2015, engaging with 207 owners. The results showed that family labor and hired labor were widely used in rubber plantations in the three communities. Locally hired laborers and laborers from other countries were the main sources of hired labor for rubber plantations. The transnational laborers were a secondary source of labor for all communities, especially the rural ones. Family labor was the main source of labor for smallholder rubber plots, especially for the urban and suburban areas. Hired labor was used in all sizes of rubber holding in rural and suburban communities and were very common in the small rubber holdings in urban areas. This shows that the rubber production sector creates employment for local people and for migrants. Furthermore, low rubber price conditions did not significantly impact labor movement in rubber plantations. However, rubber plantations in urban and suburban communities lacked labor supply due to their proximity to the larger urban center of Hat Yai city. Therefore, the low tapping intensity and generate the diversified source of income to attract young labor generation to work on the farms should be policy to maintain natural rubber production in Thailand